Relationship between structural features and in vitro release of doxorubicin from biocompatible anionic microemulsion - Formariz, T. P.; Chiavacci, L. A.; Sarmento, V. H. V.; Santilli, Celso Valentim [UNESP]; do Egito, E. S. Tabosa; Oliveira, Anselmo Gomes de [UNESP] (Elsevier B.V., 2007)
In this work structural features of anionic microemulsions, containing the pharmaceutical biocompatible components soya phosphatidylcholine (SPC), eumulgin HRE 40 (EU) and sodium oleate (SO) as surfactant, cholesterol (CHO) as oil phase and aqueous buffer were studied. Microemulsions were formulated with and without the antitumor drug doxorubicin (DOX). The various microstructures characterized in the pseudo-temary phase diagram were analyzed by polarized light microscopy, small-angle X-ray scattering (SAXS) and X-ray diffraction (XRD) as well as by their ability to incorporate and release DOX. The experimental results demonstrated a correlation between the composition, the structural features and drug delivery. It was found that at higher cholesterol contents, the crystallization of CHO polymorph phases changed the mobility of DOX molecules. Droplets were formed with short-range spatial correlation from a microemulsion (ME) with a low surfactant:oil ratio. More ordered structures with lamellar arrangements formed by the increasing of the CHO proportions in the formulation may be due to CHO crystallization. The in vitro release of DOX showed that the presence of a high content of crystalline CHO prolongs the release of DOX from ME. The retention of DOX in the internal oil phase of the ME may modulate the drug release for a prolonged time. These results clearly demonstrate the potential of ME as a drug-delivery system. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: anionic microemulsion; mesophases; drug delivery; doxorubicin; SAXD; XRD